Given that: 2tanθsinθ = 4 - 3cosθ , show that: 0 = cos²θ - 4cosθ + 2 .

Starting with: 2tanθsinθ = 4 - 3cosθ . We can rewrite tanθ in terms of sinθ and cosθ.We know: tanθ = sinθ ÷ cosθ .By substituting we get: 2(sinθ ÷ cosθ)sinθ = 4 - 3cosθ .Let's multiply out by cosθ to get: 2sin²θ = 4cosθ - 3 cos²θ .Remembering the trigonometric identity:sin²θ + cos²θ = 1 . We can find that: 2sin² = 2 - 2cos²θ .This is useful because when we substitute back into the original equation we can eliminate the 2sin²θ term.Hence: 2 - 2cos²θ = 4cosθ - 3 cos²θ .Finally rearranging we get: 0 = cos²θ - 4cosθ + 2 . Just what we wanted.

Answered by Henry S. Maths tutor

4743 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the all the angles of a triangle with side lengths of 8cm, 11cm and 11cm.


Lorem ipsum dolor sit amet


Using methods of substitution solve the following simultaneous equations: y - 2x - 1 = 0 and 4x^2 + y^2 - 25 = 0


The line AB has equation 5x + 3y + 3 = 0 . (a) The line AB is parallel to the line with equation y = mx + 7 . Find the value of m. [2 marks] (b) The line AB intersects the line with equation 3x -2y + 17 = 0 at the point B. Find the coordinates of B.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences